2016
DOI: 10.1016/j.biomaterials.2015.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Cell source determines the immunological impact of biomimetic nanoparticles

Abstract: Recently, engineering the surface of nanotherapeutics with biologics to provide them with superior biocompatibility and targeting towards pathological tissues has gained significant popularity. Although the functionalization of drug delivery vectors with cellular materials has been shown to provide synthetic particles with unique biological properties, these approaches may have undesirable immunological repercussions upon systemic administration. Herein, we comparatively analyzed unmodified multistage nanovect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…Furthermore, in vivo results demonstrated that mMSVs exhibited delayed liver accumulation and increased circulation time compared to the hMSVs. 60 These results indicate that syngeneic membrane components are necessary for effective avoidance of the mononuclear phagocyte system, an effect that is most likely due to interspecies differences in self-tolerance proteins.…”
Section: Biomimetic Msvmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, in vivo results demonstrated that mMSVs exhibited delayed liver accumulation and increased circulation time compared to the hMSVs. 60 These results indicate that syngeneic membrane components are necessary for effective avoidance of the mononuclear phagocyte system, an effect that is most likely due to interspecies differences in self-tolerance proteins.…”
Section: Biomimetic Msvmentioning
confidence: 83%
“…Syngeneic leukolike MSVs were prepared by coating particles with murine macrophage membranes (mMSV), while xenogeneic leukolike MSVs had a human T lymphocyte coating (hMSV). 60 Cell culture experiments revealed that although mMSVs and hMSVs both interacted with murine macrophages, only the former was able to avoid cellular internalization. Furthermore, in vivo results demonstrated that mMSVs exhibited delayed liver accumulation and increased circulation time compared to the hMSVs.…”
Section: Biomimetic Msvmentioning
confidence: 99%
“…Another strategy is to use biomimetic surfaces, whereby the nanomaterial surface is modified with a natural membrane coating to avoid phagocytic clearance, prolong drug circulation, and improve the biocompatibility. Markers, such as CD47 [66] or even leukocytes, are attached to the surface of the nanomaterial to camouflage it, in that the body recognizes it as 'self' [67].…”
Section: Surface Compositionmentioning
confidence: 99%
“…As NPs are in the size range of biological aggressors, interactions with the immune system are more likely to occur. Thus, a major limitation in nanomedicine is the correct evaluation of the fate of the nanodrugs as antitumoral effectors within a biological system (140)(141)(142)(143)(144)(145)(146). As nanomaterials match the same size range as biomolecules and cellular structures endows them with the propensity to reach intracellular structures previously accessible only to biological aggressors.…”
Section: Reduced Biocompatibilitymentioning
confidence: 99%